The development of polymer materials selection system using PHPMyAdmin - Mun, N. K.; Abd Manab, Mohd Fairuz; Arep @ Ariff, Hambali; Salit, Mohd Sapuan (2009)
Determination of the right material for a given engineering application is a crucial decision. Various polymer materials selection methods have been developed to assist designers to determine the right polymer for a given engineering application. This paper presents a new polymer materials selection process for natural fibre composite using expert system. The software tool has been chosen in assisting to develop the expert system, namely PHPMyAdmin. The software tool written in PHP language designed to handle the administration of MySQL server over the World Wide Web. Various polymer material properties are considered in order to develop the system. In order to demonstrate the system implementation, a car dashboard has been selected as a case study. It is showed that the polymer materials process using PHPmyadmin can assist designers to determine the right polymer for a given engineering application.